PECULIARITIES OF PHYSICAL AND MENTAL DEVELOPMENT OF PRESCHOOL CHILDREN - Gulasal Tursunaliyeva (Bright Mind Publishing, 2025)
The main task of physical education of preschool children is to direct them to early education and to ensure their desire for physical activity.
Keywords: Preschool children, raising a healthy child, physical education, development, mental preparation.